1993
DOI: 10.1021/ma00076a064
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of propagation rate coefficients using pulsed-laser polymerization and matrix-assisted laser desorption/ionization mass spectrometry

Abstract: The IUPAC Working Party on modeling free-radical kinetics' noted that pulsed-laser polymerization (PLP) (e.g., ref 2) provides ameans of measuring the propagation rate coefficient (k,) that is virtually assumption-free. PLP involves pulsed-laser illumination of monomer and photoinitiator, under conditions such that a significant amount of macroradicals is terminated by a very short radical species formed in the pulse immediately subsequent to that in which the longer macroradical was formed. If one can identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…In the current study, methyl methacrylate (MMA), ethyl methacrylate (EMA) and butyl methacrylate (BMA) were used and PLP experiments were performed over a range of temperatures to allow determination of Arrhenius parameters. This is a significant step forward from the simple analysis of model monomers MMA and styrene at constant temperature which has been attempted so far using PLP/MALDI-MS [47][48][49][50] with the exception of an elaborate study by Willemse et al on the chain length dependency of k p . [31] Benzoin was employed as the radical photoinitiator as it dissociates into two radical species of roughly the same molecular weight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, methyl methacrylate (MMA), ethyl methacrylate (EMA) and butyl methacrylate (BMA) were used and PLP experiments were performed over a range of temperatures to allow determination of Arrhenius parameters. This is a significant step forward from the simple analysis of model monomers MMA and styrene at constant temperature which has been attempted so far using PLP/MALDI-MS [47][48][49][50] with the exception of an elaborate study by Willemse et al on the chain length dependency of k p . [31] Benzoin was employed as the radical photoinitiator as it dissociates into two radical species of roughly the same molecular weight.…”
Section: Resultsmentioning
confidence: 99%
“…[45,46] MALDI-MS has been investigated as a tool to measure MWD in conjunction with PLP-experiments using methyl methacrylate and styrene as model monomers as early as 1993. [31,[47][48][49][50] Although the general applicability was demonstrated, PLP/MALDI-MS has since not made the step towards an established technique for the determination of k p . One likely reason for this has recently been summarized by Schnöll-Bitai et al, who showed that quantitative determination of MWD requires a number of data transformations to be made prior to analysis.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 More recently, it has also been used to characterize many synthetic polymers. [8][9][10][11][12] It has been shown to be a viable tool for end-group analysis as well as product confirmation for synthetic polymers. Another advantage of MALDI-TOF MS for synthetic polymer analysis is that the absolute molecular masses can be determined as opposed to relative molecular weights by GPC, and this determination is independent of polymer structures.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that the PLP method would benefit greatly if there was an alternative to GPC-MWD analysis. Danis et al 9 suggested the use of matrixassisted laser desorption ionization time-of-flight (MAL-DI-TOF) mass spectrometry (MS) for MWD analysis. Their work yielded a propagation rate coefficient significantly at odds with that obtained from GPC data.…”
mentioning
confidence: 99%